Doctrine on the Antidotal Effects of Coffee in Homoeopathy-A Review (Advancements in Homeopathic Research, 2022)
Looking at the history of coffee, it creates the context in which we can study and further understand this drink. From its discovery by Ethiopians to its present worldwide status, coffee has been fraught with controversy in medical communities. While some early doctors claimed it to be the ultimate cure all, others blamed it for being the source of all illness. Homoeopathy and coffee have a long lasting relation which started with the article “On the effects of coffee, from original observations” written by Samuel Hahnemann in 1803. Hahnemann was very critical regarding his views on coffee as a homoeopathic antidote. We also see in the writings of the earliest homeopaths a list of food and drinks allowed or forbidden, and the practitioners used to give this list to their patients and coffee is the foremost in this list. This became the reason for many homoeopathic physicians to advice their patients to avoid coffee during treatment. This review highlights the views and statements of Samuel Hahnemann and the other pioneers regarding coffee as an Homoeopathic antidote and its relationship with the concept of Homoeopathic philosophy.
Keywords: Coffee; Antidote; Homoeopathy